The 'right way' to the left chamber in non-severe COPD: Echocardiographic predictors for stress-induced left ventricular diastolic dysfunction - Radostina Cherneva; Stefan Denchev; Zheyna Cherneva (KARE Publishing, 2020)
Objective: Dyspnea is a major complaint of both chronic obstructive pulmonary disease (COPD) and heart failure with preserved ejection fraction (HFpEF). It often remains underdiagnosed in COPD patients when only echocardiography at rest is performed. The aim of this study was to evaluate the predictive value of cardiopulmonary and echocardiographic parameters at rest for the diagnosis of HFpEF in non-severe COPD patients who complain of exertional dyspnea and have no overt cardiovascular disease. Methods: A total of 104 COPD patients underwent echocardiography before cardiopulmonary exercise testing (CPET) and 1-2 minutes after peak exercise. The patients were divided into 2 groups based on peak E/e' measurements: patients with masked HFpEF-stress and left ventricular diastolic dysfunction (LVDD; E/e'>15), and patients without masked HFpEF (without stress LVDD). CPET and echocardiographic parameters at rest were measured and the predictive value for stress E/e' was analyzed. Results: Stress LVDD occurred in 67 of 104 patients (64%). These patients achieved a lower work load, lower 'VO2 consumption, lower minute ventilation, and higher 'VE/'VCO2 slope in comparison with patients without stress LVDD. None of the CPET values correlated with stress E/e'. The best independent predictors for stress LVDD were right atrium volume index (RAVI), right ventricle (RV) parasternal diameter, and RV E/A >0.75. The combination of these echocardiographic parameters predicted HFpEF with an accuracy of 91.2%. Conclusion: There is a high prevalence of stress LVDD in non-severe COPD patients with exertional dyspnea who remain free of overt cardiovascular disease. RAVI, RV parasternal diameter, and RV E/A >0.75 were the only independent predictors of stress LVDD.